Brasil holandês: os caminhos do conhecimento - Silva, Leonardo Dantas (Ciência & Trópico, 2011)
RESUMO Aborda o "Brasil Holandês", destacando a figura de mecenas do seu governador, Maurício de Nassau, e o estímulo que propiciou à produção científica e editorial sobre o País. Passa em revista os cronistas do Brasil flamengo, analisando a historiografia então produzida. Em seguida, dedica-se a comentar os estudos contemporâneos, detendo-se em nomes como José Antônio Gonsalves de Mello e Evaldo Cabral de Mello. Concluindo, refere-se ao recente lançamento do livro Guia de Fontes para a História do Brasil Holandês, patrocinado pelo Ministério da Cultura e editorialmente organizado e produzido pela Fundação Joaquim Nabuco através de sua Editora Massangana. ABSTRACT Dutch Brazil: The Paths of Knowledge. v. 30, n. 1, p. 115-140, jan./jun. 2002. The article studies the Dutch Brazil stressing friend of the arts and the sciences, Maurice of Nassau, governor of the Northeast during the Dutch occupation during the seventeenth century. He represented a remarkable stimulus to the scientific as well as in the field of publishing all over the country. The work makes a review of the writers of that period, analysing mainly the historiography produced at that times. Then comments on some contemporary studies, such as José Antonio Gonsalves de Mello and Evaldo Cabral de Mello’s work. As a conclusion, makes reference to the recent Guia de Fontes para a História do Brasil Holandês (Source Guide to the History of the Dutch Brazil), produced under the patronage of the Ministry of Culture of the Brazilian Government and editorially organized and published by the Fundação Joaquim Nabuco through its Editora Massangana. RÉSUMÉ Le Brésil hollandais: les chemins de la connaissance. v. 30, n. 1, 115-140, jan./jun. 2002. L’auteur aborde le “Brésil hollandais”, détachant la figure de mécène de son gouverneur, Maurice de Nassau, et la force qu’il a donné à la production scientifique et éditoriale dans le pays. Il passe en revue les chroniqueurs du Brésil flamand, analysant l’historiographie produite. Ensuite, il se consacre aux commentaires des études contemporaines, s’arrêtant sur des noms comme José Antônio Gonsalves de Mello e Evaldo Cabral de Mello. Il conclut en se référant au récent lancement du livre Guide des sources pour l’Histoire du Brésil hollandais, sous le patronnage du Ministère de la Culture et organisé et produit par la Fondation Joaquim Nabuco, à travers les éditions Massangana.